Agriculture for development in Iraq? Estimating the impacts of achieving the agricultural targets of the national development plan 2013–2017 on economic growth, incomes, and gender equality - Al-Haboby, Azhr; Breisinger, Clemens; Debowicz, Darío; El-Hakim, Abdul Hussein; Ferguson, Jenna; van Rheenen, Teunis; Telleria, Roberto (International Food Policy Research Institute, 2014)
This paper estimates the potential effects of achieving the agricultural goals set out in Iraq’s National Development Plan (NDP) 2013–2017 using a dynamic computable general equilibrium model. The findings suggest that raising agricultural productivity in accordance with the NDP may more than double average agricultural growth rates and add an average of 0.7 percent each year to economywide gross domestic product during the duration of the plan. As a consequence, the economy not only diversifies into agriculture, but agricultural growth also lifts growth in the food processing and service sectors.